Advanced introduction to critical global development - Kothari, Uma; Klein, Elise (Cheltenham Edward Elgar, 2023)
This stimulating and accessible Advanced Introduction critically engages with dominant, modernist and ahistorical narratives of development, foregrounding the overlooked dissonant discourses that are largely written out of mainstream development. It argues that development discourse and practice must remain aware of how historically unequal relations continue to be reproduced today and outlines a range of effective strategies for guiding change towards achieving global social justice.
Keywords: Economic development; Development economics; Social change--Economic aspects